Evaluation of the implementation of the Elderly Posyandu during the Covid-19 pandemic in Jambi City - M. Ridwan; Puspita sari (Lembaga Pengembangan Kinerja Dosen, 2022)
Elderly background is defined as someone who is already 60 years old and above. Posyandu Lansia is an activity in community health services and family health services in a certain community-driven area where they can get health services. This study aims to determine the implementation of posyandu for the elderly during the Covid-19 period at the Putri Ayu Health Center, Jambi City. Method: this research method is qualitative. Data collection was carried out by in-depth interviews of 12 informants, selection of informants by purposive sampling. Result: The posyandu for the elderly in the work area of the putri ayu health center is not constrained by facilities and infrastructure. The Health Office provides an support in the form of facilities and infrastructure. Operational costs have been assigned to the elderly Posyandu so that it can run well. When Covid 19 occurred, all posyandu activities of the elderly stopped. Conclusion: Elderly people cannot be done during the Covid-19 pandemic due to the outbreak and the government's policy of limiting activities during the Covid-19 period.